Factors Associated with Complaints of Hearing Impairment in Workers in the Wet Production Section at PT HEVEA MK I Palembang in 2023 - Rio Purnama; Sari Ilda febriyanti; Aisyah Ananda (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Advances in science and technology have driven the rapid rate of industrialization and contributed to the success of improving the quality of life and welfare of mankind. The application of advanced technology and equipment on the one hand creates ease in production, in larger quantities, higher quality and in a relatively short time, but on the other hand tends to increase work risk or hazard, as well as the possibility of increasing problems and incidence of disease due to Work. This research was conducted with the aim of knowing the factors associated with complaints of hearing loss in the wet production section of PT HEVEA MK I Palembang in 2023. This research method uses a cross-sectional method, which is a study in which the independent and dependent factors are examined simultaneously. in the same time period. To obtain data in the field, it was carried out by measuring noise intensity in the production work area and distributing questionnaires to 49 respondents who were working. The conclusion of the study showed that there was a relationship between noise intensity (P=0.001), working time (P=0.017), work period (P=0.022), and use of ear protection devices (P=0.000) with complaints of hearing loss in production workers wet at PT. HEVEA MK I Palembang in 2023.